SUSTAINABLE ENTREPRENEURSHIP ANALYSIS OF THE COMPETITIVE ADVANTAGES OF MSMES IN THE GREEN ECONOMY ERA IN BANYUASIN REGENCY - Syahrizal Bin Muhammad Syafii; Rahma Rahma; Andika Ramadani; Tia Wati (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE This study aims to test the influence of sustainable entrepreneurship (through hydroponic technology) on marketing strategies and the competitive advantage of MSMEs in Banyuasin Regency, using a quantitative approach. The efficiency of environmentally friendly technology is explored as a driver of competitiveness. Consumer awareness was tested as a moderation variable that affects the relationship between factors.METHODOLOGY – The methodology used was a census, with data collected through an online questionnaire from 89 hydroponic MSMEs in the region. The analysis used Moderated Regression Analysis (MRA) through three regression models (direct effects, moderation, and interaction). Research limitations include the challenge of measuring unobservable variables and establishing cause and effect relationships.FINDING – The findings show that resource efficiency, product innovation, and technology significantly affect the competitiveness of hydroponics, although the effect of product and technology innovation is relatively weak. Resource and technology efficiency also have a positive impact on consumer awareness, but product innovation does not. However, consumer awareness was found to not significantly affect competitiveness, nor did it moderate the relationship between efficiency, innovation, technology, and hydroponic competitiveness.